The risk levels of pressure ulcer among critically ill patients in the Intensive Care Unit (ICU): A survey study - Putri, Fitri Yeni; Chaidir, Reni; Suparman Rustam, Junaidy (Nurse Point: Journal of Nursing, 2025)
Introduction: Pressure ulcers represent a significant global challenge, associated with increased mortality, morbidity, healthcare expenses, and extended stays in the Intensive Care Unit (ICU). This issue reflects the persistent prevalence of pressure ulcers, often compared to an iceberg phenomenon, as they continue to exist year after year. Objectives: The primary objective of this study is to evaluate the risk levels of pressure ulcers among critically ill patients at the Yarsi West Sumatra Hospital in 2024. Methods: This research utilizes a quantitative design, focusing on all patients admitted to the ICU. An infinite population sampling technique was employed, resulting in a total sample size of 97 respondents. Results: The findings revealed that the most prevalent age group among respondents was between 55 and 70, comprising 39 individuals (40.2%). Most respondents were female, totaling 54 individuals (55.7%). The length of hospital stay most commonly reported was 2 days, with 52 respondents (53.6%) falling into this category. Conclusions: An analysis of pressure ulcer risk levels indicates that less than half of the critically ill patients are at high risk for developing pressure ulcers, with 40 respondents (41.2%) identified in this category. Conversely, most 57 respondents (58.8%) are at low risk for developing pressure ulcers.